PENGARUH BAYANGAN TERHADAP OUTPUT TEGANGAN DAN KUAT ARUS PADA PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) - Hattu P D Edwin; Wabang A Jhon; Tuati Ambros; Palinggi Aris (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2018)
Electrical energy is a very important requirement for the community, along with the development of the era and technological advances that are urgently needed, the need for electrical energy is very large, while the source of electricity that is currently being used still uses energy derived from fossil fuels. As we know that the source of energy derived from fossils is very limited, therefore other energy sources are sought or we are more familiar with renewable energy, one of which is the energy source that comes from the sun, which is better known as solar cell. The electricity from this solar cell is very dependent on sunlight which must illuminate the solar panels so that solar energy can be converted into electrical energy. The output from these solar panels is in the form of voltage and electric current. Some factors that can affect the amount of output or output voltage of electric current in PLTS is, temperature, shadow, (cloud condition, and surrounding environment), and wind speed. Therefore, the purpose of this research is to find out how much the shadow effect on the output voltage and electric current produced by PLTS. It is expected that this research can increase the knowledge of energy derived from the sun in this case the solar cell and know the effect of the shadow on the output voltage and electric current from solar panels.The results showed that there was a shadow effect on voltage reduction and current strength in the PLTS system, namely the 10% shadow area and 12.44 volt DC solar panel current and 2.54 amperage, 100% area covering the voltage output panel and the current of solar panels 12.10 volt DC and 0.22 amperage. The area of the shadow that covers the solar panel affects the output voltage and the strong current of the battery that is the area of the shadow 10% voltage and strong current battery 12.35 volt DC and 18.54 amper, 100% area cover the output panel voltage and strong current battery 11.90 volt DC and 13.85 amperes The shadow area covering the solar panels influences the output voltage and current strength of the inverter, namely the area of the shadow 10% voltage and 226.4 volt AC inverter current and 0.97 amperage, 100% covering the output voltage panel and 220.2 volt AC and 0.66 amperage current. Keywords: Electrical energy, Solar cell, Shadow (cloud condition)